COMPARISON OF HAND DYNAMOMETERS IN ELDERLY PEOPLE - Guerra, RS (2009)
Objective: Some dynamometers previously tested in healthy adults showed variable degrees of practicality, weight and ergonomics. More practical models could also be used as a more suitable tool in gerontological field and clinical studies. The purpose of the present study was to evaluate the reliability of the measurements and the performance of hand grip strength dynamometers in the elderly. Study design: Cross-sectional study. Setting: A retirement home and a social day care centre for old people in Porto, Portugal. Participants and measurements: The accuracy of four static grip strength dynamometers (Smedlay's (R) Hand, Sammons Preston Rolyan (R) Bulb, Eisenhut (R) and the Jamar (R) Hydraulic Hand) was first tested in laboratory. The grip strength of fifty-five elderly individuals 65-99 years was measured with the four dynamometers and the Jamar (R) Hydraulic Hand which was used as the comparison dynamometer. Results: The accuracy of the four dynamometers measurements compared to known forces was excellent (r > 0.96). A strong association between the measurements obtained by the Jamar (R) Hydraulic and the other instruments evaluated was found (r > 0.77) but significant differences between the mean hand grip strength values evaluated with the Jamar (R) Hydraulic and each one of the other dynamometers were found. The Bland and Altman plots confirmed that none of the three dynamometers reflects a good agreement with the Jamar (R) Hydraulic. Conclusion: All four dynamometers showed excellent results regarding their laboratory tested accuracy. However, their application among elderly people rendered very different results. The Smedlay's (R) results' were closer to the Jamar (R) Hydraulic, though none of these three dynamometers produced comparable results to the Jamar (R) Hydraulic.